Penerapan Kurva Bezier Karakter Simetrik dan Putar pada Model Kap Lampu Duduk Menggunakan MAPLE - Juhari, Juhari; Octafiatiningsih, Erny (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2015)
This research aimed to obtain construction procedures lampshade form through incorporation and election of parameters shape shifter Bezier surface. Thus, it product a sholid lampshade that both symmetrical and varied. In contruction lampshade it requires learning about the physical (expose) and geometrical aspects. In terms of geometry model-making of lampshade sitting which has existed in general still monotone and built of object cut model. Dealing with the problem, so this research is divided into four stages: Firstly, prepare the data of building sitting lampshade. Secondly, study about technique of building symmetrical sitting lampshade. Thirdly, construct overall lampshade. The results of this research is procedures by contruction of sitting lampshade: First, The main axis split into three sub segments axis non-homogeneous. Second, build parts of the sitting lampshade (the base, the main part, the roof) by combining the components lampshade deformation results geometry objects. Third, fill each sub-segment of non-homogeneous parts with parts of the lampshade and build a boundary curve resulting lampshade varied models, innovation, and symmetry.